Awareness on Ebola Virus among Undergraduate Dental Students in a Private Dental Institution, Chennai - A Questionnaire Survey - S.Divyashri1 , V. Vishnu Priya2 , R.Gayathri3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Ebola virus disease (EVD) is a deadly disease with occasional outbreaks that occur primarily on the Africancontinent. EVD most commonly affects people and nonhuman primates (such as monkeys, gorillas, andchimpanzees).The aim of the study to determine the awareness of Ebola virus among the undergraduatedental college students.This study involved the awareness of Ebola virus in the age group of 18 to 25 years. Awell structured questionnaire comprising 14 questions covering socio demographic information, knowledge,attitude, perception was framed and administered to the participants through an online google forms. Surveywas conducted among 100 college students. In that 30.39% male students and 69.61% of female studentshave taken this survey. The association between groups was assessed by Chi Square test where p < 0.05was considered statistically significant. We have observed that association between gender and responsesto awareness on the mode of spread of Ebola virus was statistically significant (p =0.020 ). The awarenesson ebola virus was analysed among the few college students by this survey and more awareness should becreated among the population about the ebola virus.